2018
DOI: 10.25258/ijpqa.v9i4.14538
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses' Knowledge about Nosocomial Infection at Burns Units in the Middle Euphrates Teaching Hospitals

Abstract: Background: Nosocomial infections (NIs) are considered the major and common healthcare problems in most healthcare settings at most of developing countries like Iraq, important to assess the nurses' knowledge level and identifying gaps of their knowledge about NIs. Objectives: To assess the nurses' knowledge about nosocomial infection, and to find out the relationship between nurses' knowledge about nosocomial infection and selected demographic variables. Methodology: A descriptive study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The results declared that the majority of the educational levels were nurses who graduate from nursing secondary school (n= 82; 45.6%), because the school was the oldest in comparison with the institute and college of nursing; in addition, the college was recently formed in Wasite Governorate. These results are supported by the study of AL-Salih (14), which mentioned that the nursing secondary school had the highest percentage (55%).…”
Section: Discussionsupporting
confidence: 54%
“…The results declared that the majority of the educational levels were nurses who graduate from nursing secondary school (n= 82; 45.6%), because the school was the oldest in comparison with the institute and college of nursing; in addition, the college was recently formed in Wasite Governorate. These results are supported by the study of AL-Salih (14), which mentioned that the nursing secondary school had the highest percentage (55%).…”
Section: Discussionsupporting
confidence: 54%
“…Another study conducted in 2018 to assess the knowledge of nurses regarding prevention of infection among burn patients and results revealed that that the majority 69.8% of nurses had passed score of knowledge regarding nosocomial infection in burns' units at middle Euphrates teaching hospitals.in addition, the present study pointed out there was a significant relationship between nurse knowledge and number of training courses about nosocomial infection (AL-Salih et al, 2018).…”
Section: Review Of Literaturesupporting
confidence: 52%
“…Reducing the spread of disease and human care services related burn infection in the burn unit of public hospital (El-Maghawry, El Nem, Sherif, & Hagag, 2016). Burn infection are viewed as the major and basic healthcare services issues in most social insurance settings all things considered of developing nations (AL-Salih, Muhbes, & Hindi, 2018). Contamination is one of the primary difficulties among burned patients.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a study conducted by (23) among nurses revealed that, there was no signi cance relationship at p > 0.05 between nurse's age and their knowledge toward nosocomial infection prevention. Similarly, another study conducted among nurses by (24) to assess the nurses' knowledge about nosocomial infection at burns' centers and units in the middle Euphrates teaching hospitals revealed that, there was no signi cant relationship between the nurse's knowledge about NIs prevention and their ages at p-value (> 0.05).…”
Section: Agementioning
confidence: 97%